Cardboard formulation made from banana stalks and coconut coir using linear programming method - Azimmatul Ihwah; Retno Astuti; E. F. Sri Maryani Santoso; Afifah Ulfah (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
Malang Regency produced 690,136 tons banana in 2016. The banana production is in line with the waste (banana stalks). Banana stalks contain 83.3% cellulose and 2.97% lignin, of which can be used as raw material for paperboard making. However, the banana leaf paper has a low tensile strength of 7.45 N/mm2, so additional fibers to strengthen the paper is necessary, such as coconut coir which has a tensile strength of 46.67 N/mm2. This research aimed to formulate the material for paper making, such as the fiber source (banana fronds and coconut coir), filler (tapioca), and water to produce paperboard with minimal costs. The research was conducted using a linear programming method with LINDO software. The formulation of a sheet of cardboard produced was 34.79 g of dry banana stalks, 19.20 g of coconut coir, 6.00 g of tapioca, 136.08 g of NaOH, 2080 mL of distilled water, and 1000 mL of water with manufacturing cost of IDR 6,931.15. The paper characteristics has gramature of 323.8 g/m2, moisture content of 19.75%, water absorption test of 743.2 g/m2, tensile resistance of 1.4 kN/m, and stiffness of 5.7 mN.m.